Bhada Tharu Homestay: Building National Integrity through Cultural Performance - Dangaura, Mohan (Molung Educational Frontier, 2021)
This article studies the challenges of modernity in Tharu people’s way of life and how successfully they have sustained to maintain aesthetics of ethnicity coping together with modernity. The scholarly discussion of the impact of ritual performances of Tharu people to identify themselves in the national and international domain through the socio-cultural aspect of homestays provides us insight into how Tharus have become successful in preserving the memory of identity through cultural heritage. This study confines its approach within the Bhada village of Kailali district. It examines the progressive changes institutionalized after the homestay programmes in socio-cultural development of Tharu people’s cultural performances facing urbanization. Homestay programmes in the Tharu village of Kailali district have accelerated their financial advancement chiefly by their exceptionally distinct social-cultural legacies of rituals and performances. With the assistance of various exploration reports, it essentially analyzes the part of social execution like dance melodies among Tharu people to bear the progressions for economic exercises and vocation. With the assistance of Devkota and Bhattarai’s notion of homestays and rural development, the paper legitimizes the imminent practical development in the indigenous community by analyzing the issues from culture to modernity.